Content and Structure of Psychological Readiness of Secondary School Students to Solve Creative Mathematical Tasks - Danyliuk, Ivan; Bonchuk, Natalia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2021)
Informational technologies, the latest challenges in the field of technical development of society condition irreversible environmental and human changes. In the context of these changes a special place is occupied by those activities that are directly or indirectly related to technical, cybernetic, mathematical activities. This actualizes the manifestation of mathematical abilities, giftedness for math activity in youth, features of creative potential, etc.The purpose of the study is to clarify the content and structure of psychological readiness of high school students for creative mathematical performance. The main content characteristics of the creative mathematical problem as a model for the study of creative mathematical activities are considered in the article. Based on the theory of learning problems, the psychological structure of mathematical task is determined. The structure contains the following components: a) the subject of the task (in its initial state or the ascending subject of the task); b) the model of desired state, ie the requirements (set and required) of the task.The contradiction of the creative mathematical situation first of all characterized by the object and subject of the creative mathematical task.The psychological readiness of high school students for creative mathematical performance is an integrated personality trait aimed at realizing of the cognitive abilities of young people in the process of solving creative mathematical problems. Since the process of creative mathematical thinking (creative mathematical activity) is determined by objective (subject-functional) and subjective-personal (motivation, emotional-volitional, value attitude) components, it is worth saying about subject-functional, subjective-personal types of psychological readiness of high school students to perform mathematical creative activities.
Keywords: psychological readiness for creative performance; subject-functional readiness; subjective-personal types of psychological readiness of high school students; content of psychological readiness of high school students for creative mathematical activity